Study of binary mixtures of Tribulus terrestris extract and Quillaja bark saponin as oil‐in‐water nanoemulsion emulsifiers - Schreiner, Tatiana B. (2023)
Several industrial fields use emulsifiers in their products, with the ones of natural origin gaining increasing relevance. Identifying and using diversified sources for their extraction is a pertinent topic regarding sustainability principles, biodiversity preservation, or cost rationalization. This is the case of Quillaja bark saponin (QS), for which saponin-rich extracts, for example, Tribulus terrestris (TT), are being highlighted as viable alternatives, even though constraints like performance are still on the table. In this context, an experimental design using binary emulsifier mixtures of TT with pure QS was carried out by changing their composition (50–90%wt. TT), content (1.5–4.5%wt.), and high-pressure homogenization conditions (5–15 cycles). The emulsions were characterized by zeta potential, morphology, droplet size, and stability (expressed as the number of days without creaming formation). Moreover, the cream index for 30 days was determined to indicate the destabilization extent. The zeta potential showed stable emulsions (values below 41 mV); even still, creaming formed for samples using a low emulsifier and high TT contents. The emulsions’ mean droplet diameter (D [3, 2]) was between 78 and 921 nm, with smaller sizes agreeing with higher stability. The statistical analysis indicated an optimum composition range comprising an emulsifier content between 3.9 and 4.5%wt. and TT content between 50 and 56%wt. to reach stable products. Overall, TT can provide an effective solution when combined with QS, decreasing the dependence on Quillaja bark.